DETERMINANTS ANALYSIS OF BEHAVIORAL INTENTION AND USE BEHAVIOR OF THE NEW SAKPOLE APPLICATION, USING THE UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY 2 (UTAUT2) MODEL - Aisah, Siti; Handoyono, Rudi; Farizi, Musyafa Al (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2024)
Sakpole is a motor vehicle tax payment system for taxpayers in Central Java Province. This study aims to analyze the factors that affect the